Manajemen Koperasi Dalam Rangka Pengelolaan Hutan Rakyat Dan Pengaruhnya Terhadap Ketahanan Ekonomi Masyarakat (Studi Pada Koperasi Wana Lestari Menoreh Di Kabupaten Kulon Progo Diy) - Imam Subekti; Edhi Martono; Edy Suandi Hamid (Universitas Gadjah Mada, 2016)
ABSTRACTThis study identified KWLM management in public forest management and analyzed the effect of cooperative management in public forests management to economic resilience of society of KWLM members. It took at Koperasi Wana Lestari Menoreh in Kulon Progo.This study used combination method with